Nickel‐Promoted Highly Regioselective Carboxylation of Aryl Ynol Ether and Its Application to the Synthesis of Chiral β‐Aryloxypropionic Acid Derivatives. Issue 5 (25th February 2015) - Saito, Nozomi; Sun, Zhongdong; Sato, Yoshihiro
Abstract Nickel(0)‐promoted carboxylation of aryl ynol ether proceeded in a highly regioselective manner to produce α‐substituted‐β‐aryloxyacrylic acid derivatives. The α‐substituted‐β‐aryloxyacrylic acids were transformed into the corresponding β‐aryloxypropionic acid derivative as an optically active form via rhodium‐catalyzed asymmetric hydrogenation.